A multilevel consideration of service design conditions: Towards a portfolio of organisational capabilities, interactive practices and individual abilities. Issue 2 (13th March 2017) - Karpen, Ingo Oswald; Gemser, Gerda; Calabretta, Giulia
Abstract : Purpose: The purpose of this paper is to advance the current understanding of organisational conditions that facilitate service design. Specifically, the focus is on organisational capabilities, interactive practices and individual abilities as units of analysis across service system levels. Grounded in design principles, the paper conceptualises and delineates illustrative service design conditions and introduces a respective service design capability-practice-ability (CPA) portfolio. In doing so, an emerging microfoundations perspective in the context of service design is advanced. Design/methodology/approach: Conceptual paper. Findings: This paper identifies and delineates a CPA that contributes to service design and ultimately customer experiences. The service design CPA consists of six illustrative constellations of service design capabilities, practices and abilities, which operate on different organisational levels. The service design CPA builds the foundation for in-depth research implications and future research opportunities. Practical implications: The CPA framework suggests that if an organisation seeks to optimise service design and subsequent customer experiences, then individual- and organisational-level (cap)abilities and interactive practices should be optimised and synchronised across specific CPA constellations. Originality/value: This paper provides the first microfoundations perspective for service design. It advances marketing theory through multilevel theorising around service design capabilities, practices and abilities and overcomes extant limitations of insular theorising in this context.